MENANAMKAN NILAI-NILAI KESEJARAHAN DALAM PEMBELAJARAN SEJARAH MELALUI PUISI KEPAHLAWAN - Ateng Rasihudin (Jurnal Artefak, 2019)
Instilling historical values (internalization) can be developed by history teachers through reading poetry of heroism, because the process of reading heroic poetry is able to shape the atmosphere and inspiration of readers and listeners so that they will be able to give a deep message of value to students. This research is a Classroom Action Research with a qualitative approach. Data collection techniques used in this study were: observation, field notes, documentation, and interviews. The data source is students of class XI IPS-1. This research was conducted in four cycles with seven actions. The findings in this classroom action research are that through reading poetry of heroism in history learning can instill students' historical values, through the stages of value transfer, value transactions, and trans value internalization so that the formation of established student personality and character is formed. This can be seen from the results of observations and interviews in four cycles carried out.